2020
DOI: 10.3390/ijerph17020396
|View full text |Cite
|
Sign up to set email alerts
|

Gender Informed or Gender Ignored? Opportunities for Gender Transformative Approaches in Brief Alcohol Interventions on College Campuses

Abstract: Brief alcohol interventions are an effective strategy for reducing harmful and risky alcohol use and misuse. Many effective brief alcohol interventions include information and advice about an individual’s alcohol use, changing their use, and assistance in developing strategies and goals to help reduce their use. Emerging research suggests that brief interventions can also be expanded to address multiple health outcomes; recognizing that the flexible nature of these approaches can be helpful in tailoring inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
(150 reference statements)
0
11
0
Order By: Relevance
“…Once we sifted through these, we found that the muddy conceptual use of sex and/or gender prevented us from confidently carrying out our intended overarching systematic review. Instead, based on this material, we developed several scoping reviews [5,16,18,19] and one small systematic review [17] because terms were either misused or imprecise, or in some cases conflated or used in contradictory ways in a single article. Our intention for systematically surveying the current evidence on sex, gender and substance use was undermined because precise engagement with sex and gender in research was, in essence, missing in action.…”
Section: Issues With Language and Conceptual Claritymentioning
confidence: 99%
See 4 more Smart Citations
“…Once we sifted through these, we found that the muddy conceptual use of sex and/or gender prevented us from confidently carrying out our intended overarching systematic review. Instead, based on this material, we developed several scoping reviews [5,16,18,19] and one small systematic review [17] because terms were either misused or imprecise, or in some cases conflated or used in contradictory ways in a single article. Our intention for systematically surveying the current evidence on sex, gender and substance use was undermined because precise engagement with sex and gender in research was, in essence, missing in action.…”
Section: Issues With Language and Conceptual Claritymentioning
confidence: 99%
“…Focusing on fathers and caregiving is a step toward more gender-transformative approaches to smoke-free home initiatives that have traditionally focused on mothers. Wolfson et al [19] directly assess the gender-transformative impact of brief interventions on alcohol, via a cogent sex and gender analysis of existing literature in that area. Similarly Stinson et al [16] address the gendered use of technology to respond to substance use treatment and interventions.…”
Section: Implications For Substance Use Research Practice and Policymentioning
confidence: 99%
See 3 more Smart Citations